التنظيمات الأساسية في عهد السلطنة العثمانية - Mochamad Hasyim (Universitas Yudharta Pasuruan, 2017)
The condition of the Islamic state (Islamic world) was bad after the fall of the Abbasid state. Then followed by three major countries. The Osmanli Devleti was the original center of Asia Minor on the northwestern tip of the Islamic world, and expanded its territory to many parts of three ancient continents: Europe, Asia and Africa, where it lived throughout Asia Minor and much of Southeast Europe, and North Africa. In the early fourteenth century, when the Osmanli Devleti was founded, this was only a small emirate within the confines of the Muslim world based on the idea of ​​an invasion of Christians. This small border country, which did not seem important at that time, gradually developed, with the annexation and annexation of the Byzantine and Balkan regions. The Osmanli Devleti has lived for more than two centuries. In this instinct, the Osmanli Devleti extended almost two hundred and thirty-one years, including conquest and cultural work carried out by every authority. In this study, researchers wanted to find the basic rules of the Osmanli Devleti.